THE GEOPOLITICAL INFLUENCE OF 'SOFT POWER' ON CENTRAL ASIAN COUNTRIES - К.С. Мухтарова; А.К. Паизова (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì)
This article examines the geopolitical influence of "soft power" on Central Asian countries. It analyzes the conceptual frameworks of "soft power" and "hard power" as tools used by states to influence economic, social, and political spheres. The study emphasizes the dynamic nature of these concepts and their relevance in the context of geoeconomic transformations. As well as it highlights important geoeconomic and geopolitical features of "soft power" employed by leading global players, including the European Union, Iran, China, Russia, the United States, Turkey, and Japan, towards Central Asian countries. The article examines the key role played by instruments such as educational projects and grants, cultural diplomacy, and the provision of loans and other types of financial assistance. These tools are particularly important in the struggle for geopolitical influence, with non-governmental organizations, socio-cultural institutions, and charitable initiatives playing a leading role. At the same time, the study recognizes the potential of "soft power" applied by Central Asian states themselves, especially Kazakhstan, which positions itself as a dynamically developing country in the post-Soviet region. The article concludes with an analysis of the multifaceted nature of "soft power" and the difficulties in measuring it, as well as the challenges in assessing the influence of various actors. It emphasizes the dynamic nature of "soft power" and its evolution as a strategic tool for countries seeking to exert global influence. The study underscores the need for comprehensive approaches to understanding "soft power," taking into account its historical, cultural, and political context. Overall, the research contributes to the understanding of "soft power" as a key element in shaping modern geopolitics and highlights its relevance in the context of Central Asia's strategic importance. It offers valuable insights into the complexities of interstate interactions and the ongoing struggle for influence in the region. Keywords: International relations, soft power, Central Asia, geopolitics, geoeconomics, influence, education, socio-cultural diplomacy.